Float flexible land on aquatic terrain : modular water-based architecture for waterside communities in Barangay Tanza - Ong, Patricia Lauren H.
this thesis research explores the use of water-based architecture modules as an alternative, typology for waterside developments. This thesis focuses on the programmatic combinations, criteria for combinations, and feasibility of water-based architecture. The main goal of this research is to provide a structural prototype and a criterion to allow this type of development to be applied in various settings. The initial site observation was done along a river located in Tanza, Navotas City. The local presented various socio-economic and environmental implications brought about by the rapid urbanization in the area. The initial approach examines and relates various waterside and waterborne functions to the existing land use from which the program was derived. The prototyping of the floating modules, as well as its other structural components, involved various computations to determine the feasibility and the effectivity to be implemented in a real-life setting.